Evaluating the protective effects of Panax bipinnatifidus Seem. extracts on hypoxia/reoxygenation-subjected cardiomyocytes - Vu Thi Thu; Ngo Thi Hai Yen (Vietnam Journal of Science, Technology and Engineering, 2022)
The search for new products to treat ischemic heart diseases has interested scientists for years as it is the main cause of cardiovascular disease mortality. In this study, we evaluated the protective effects of Panax bipinnatifidus Seem. extracts (PSE) on hypoxia/reoxygenation (HR)-treated rat H9C2 cardiomyocytes. Rat H9C2 cardiomyocytes were either grown under normal condition or subjected to HR conditions. NecroX-5 (10 μM) was used as positive control for cardiac protective effect. The PSE (5-500 µg/ml) was employed to culture media at the onset of reoxygenation. Cell viability and mitochondrial function were tested using a Cell Counting Kit-8 and suitable fluorescence kits. The obtained data shows that HR conditions dramatically induced H9C2 cell death (p<0.05). Treatment of PSE (5-62.5 µg/ml) effectively reduced HR injuries in a dose-dependent manner. Similar to the NecroX-5 group, ginseng extract-treated cells had higher viability levels compared to that of the HR-subjected cells (p<0.05). In addition, supplementing PSE at the onset of reoxygenation strongly prevented the collapse of mitochondrial membrane potential and reduced mitochondrial oxidative stress (p<0.05). This study suggested the total saponin extracts from Panax bipinnatifidus Seem. exerts cardioprotective properties against HR damage.